The Impact of Applying Egyptian Regulations on the Lessor Business Health (Panel Data Approach) - Elewa, May Mahmoud; Mahmoud, Yasmin Abdel aal (International Journal of Accounting and Financial Reporting, 2022)
The aim of this study is to indicate the non-financial institutions financial health before and after the application of the Egyptian Financial Leasing and Factoring Act. Lessor firms applied the new Regulations for leasing on the year 2018. The study uses numerical data for 5 years during 2016-2020 from the financial reports of 10 lessors listed in the Egyptian Financial Regulatory Authority FRA. The sample of the study was equivalent to 43 firm year observations. The selected firms operate in cash, have annual reports that date from 1/1 to 31/12, have not been disqualified at any time during the study period, have complete data, and currency recorded in Egyptian pound. The test tool used to forecast financial health was the adjusted Altman Z-Score model (1995). In addition, the study applied the simple regression model and five step panel analyses. The dependent variable was the firm health represented by the sum of Z-Score. The independent variable was the Financial Leasing and Factoring Act represented by sales, financial liabilities, EBIT/operating profit or loss and financial leased fixed assets. The results indicate a strong significant impact of applying the Financial Leasing and Factoring Act on the lessor business health. The results of this study might increase the quality of predictability of lessor financial health. The length of the study period makes it possible to track progress of lessor firms to be able to predict their future business health. This is a modest contribution to the literature relating to lessors in Egypt.